(untitled) (Swiss Medical Weekly, 2013)
PRINCIPALS: Accidents in agriculture are a problem of global importance. The hazards of working in agriculture are manifold (machines, animals, heights). We therefore assessed injury severity and mortality from accidents in farming. METHODS: We retrospectively analysed all farming accidents treated over a 12-year period in the emergency department (ED) of our level I trauma centre. RESULTS: Out of 815 patients 96.3% were male and 3.7% female (p <0.0001). A total of 70 patients (8.6%, 70/815) were severely injured. Patients with injuries to the chest were most likely to suffer from severe injuries (odds ratio [OR] 9.45, 95% confidence interval [CI] 5.59–16.00, p <0.0001), followed by patients with injuries to the abdomen (OR 7.06, 95% CI 3.22–15.43, p <0.0001) and patients with injuries to the head (OR 5.03, 95% CI 2.99–8.66, p <0.0001). Hospitalisation was associated with machine- and fall-related injuries (OR 22.39, 95% CI 1.95–4.14, p <0.0001 and OR 2.84 95% CI 1.68–3.41 p <0.001, respectively). Patients suffering from a fall and patients with severe injury were more likely to die than others (OR 3.32, 95% CI 1.07–10.29, p <0.037 and OR 9.17, 95% CI 6.20–13.56, p <0.0001, respectively). Fall height correlated positively with the injury severity score , hospitalisation and mortality (all p <0.0001). CONCLUSION: Injuries in agriculture are accompanied by substantial morbidity and mortality, and range from minor injuries to severe multiple injuries. Additional prospective studies should be conducted on injury severity, long-term disability and mortality.